Os reflexos das decisões do Supremo Tribunal Federal sobre a coisa julgada tributária - Nomura, Rogério Hideaki (2017)
The purpose of this essay is to analyze the reflexes of Federal Supreme Court’s decisions pronounced within the framework of constitutional control on the prospective effects of final and unappealable decisions on the merits rendered in individual cases which involve a continuous or successive tax law relationship. The study of the behavior of the res judicata on the definitive solutions given by the Supreme Court is relevant due to the necessary provision of a solution that, on the one hand, meets certain principles, and on the other, favors the stability of legal relations. Essential to the accomplishment of this work was the study of the principles of Legal Security, Equality, Legality, Universal Jurisdiction, as well as other subjects related to the matter analyzed, and the exposition of some doctrinal positions and jurisprudence. It was concluded that Federal Supreme Court’s decisions have a substantial influence on the future effects of unappealable decisions on the merits resulting from individual lawsuits, the effects of which will cease after the publication of a Federal Senate Resolution or a judgment issued by the Supreme Court in diffuse or abstract constitutional control when a new decision is rendered in another lawsuit